Distribution and seasonal fluctuations of Ae. aegypti and Ae. albopictus larval and pupae in residential areas in an urban landscape - Rajarethinam, Jayanthi (2021)
Dengue, a vector-borne disease spread by Aedes mosquitoes, is a global threat. In the absence of an efficacious dengue vaccine, vector control is the key intervention tool in Singapore. A good understanding of vector habitats is essential to formulate operational strategies. We examined the distribution, long-term trend and seasonality of Aedes data collected during regulatory inspections in residences and public areas from 2008 to 2017. We also studied the seasonality of climate factors to understand their influence on the detection of Aedes-positive containers. The most frequently reported Aedes-positive containers were domestic containers, drains, discarded receptacles, ornamental containers, flower pot plates/trays, plants, gully traps, canvas/plastic sheet, bins, ground puddle, inspection chambers and roof tops/gutters. We found more Ae. aegypti and Ae. albopictus-positive containers per inspection in residences and public areas, respectively. The seasonality of Ae. aegypti-positive containers in residences and public areas coincided with that of mean temperature. However, the seasonality of Ae. albopictus-positive containers lagged by one month compared to that of mean temperature. Our study demonstrates the seasonal fluctuations of Aedes-positive containers in an urban environment. Understanding the distribution and seasonality of Aedes breeding helps to facilitate resource planning and community awareness to moderate dengue transmission.